KETELADAN GURU PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH MUHAMMADIYAH 1 MEDAN - Dianto, Dianto (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This research was conducted in Madrasah Aliyah Muhammadiyah 1 Medan and aimed to know: 1) Exemplary behaviour of Islamic studies teachers in Madrasah Aliyah Muhammadiyah 1 Medan. 2) Exemplary behaviour of Islamic studies teachers in fostering students? discipline in Madrasah Aliyah Muhammadiyah 1 Medan. 3) Exemplary behaviour of Islamic studies teachers in developing students? interest for studying in Madrasah Aliyah Muhammadiyah 1 Medan. 4) Students? views and opinions about the exemplary behaviour of the Islamic studies teachers in Madrasah Aliyah Muhammadiyah 1 Medan.This research was qualitative research. Qualitative methods were used because the problem was not clear, dynamic, and full of meaning so it was impossible to obtain and process the data on that social situation by applying quantitative research methods. Subjects in this study were four teachers of Islamic studies i.e. Qur?an Hadith (Al-quran Hadits), Islamic Faith and Moral (Akidah Akhlak), Islamic Jurisprudence (Fiqh), and History of Islam (Sejarah Kebudayaan Islam).Results of the study indicated that exemplary behaviour of teachers as parents in madrasah was very influential in leading the students to be a faithful, moral and educated generation. Islamic studies teachers already have the attitude of manners, discipline, achievement and the values of devotion to Allah. Furthermore, the teachers of Islamic studies in Madrasah Aliyah Muhammadiyah 1 Medan also have many good characters such as patient, authoritative, friendly, hard-working and responsible. Teachers? efforts in Madrasah Aliyah Muhammadiyah 1 Medan in creating students? interest in studying and discipline were begun from the teachers themselves as role models for students whom they show their patience and sincerety in teaching to.